Ray Launching Modeling in Curved Tunnels with Rectangular or Non Rectangular Section - Masson, Émilie; Combeau, Pierre; Cocheril, Yann; Aveneau, Lilian; Berbineau, Marion; Vauzelle, Rodolphe (IntechOpen, 2013)
None